MULTISENSORY FLAVOR PERCEPTION IN YOUNG CHILDREN - Colbert, Sarah Elizabeth (Wake Forest University, 2021)
Flavor perception is a key factor in dictating food choice, which directly relates to health outcomes. Between ages 2 and 6, children experience changes in food attitudes. This project examines the potential contribution of gustatory and retronasal olfactory perception to these behaviors. Although taste preferences are stable from birth, there is no knowledge of the development of retronasal smell perception, partly due to the difficulty in assessing sensory function in toddlers. Thus, the primary goal of this study is to implement a novel protocol for assessing flavor preference in toddlers to investigate changes in retronasal odor perception. Subjects were recruited and tested in the local community. Young children (n=22) and one of their parents (n=24) were asked to drink 8 solutions with either a taste or an odor compound, or plain water. Participants rated the solutions on a pictorial liking scale. Ratings from all solutions were analyzed to determine perceived intensity and valence. Taste intensity and valence were confirmed to be stable, but there were differences in individual odor valences and intensity of hibiscus odor in children compared to adults. This suggests that aspects of retronasal odor perception differ between children and adults and can potentially be modified by experience.
Keywords: CEBQ; childhood obesity; eating behavior; flavor perception; odor; retronasal olfaction